PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA MELARIKAN WANITA YANG BELUM CUKUP UMUR PUTUSAN /36/Pid.B/2019 PN GST - Sinta Nuriyah; Ahmad Mahyani (Gapenas Publisher, 2023)
This type of crime against human freedom in Chapter II Chapter XVIII of the Criminal Code, which is specifically investigated in Article 332 of the Criminal Code, which means running away from an underage woman. This study explains the criminal responsibility of elderly women who have run away and legal considerations for judges deciding crimes where elderly women are not sufficient. This study uses normative research, due to criminal acts that run away from immature women. The application of punishment is not in accordance with Article 332 of the Criminal Code, namely the conflict between Article 332 of the Criminal Code and the judge's decision. People who run away with too few women can only be held accountable if they meet the criteria of criminal responsibility, in this case they can be sentenced to a maximum of 7 years in prison according to Article 332 Paragraph (1) 1st of the Criminal Code. The basis for the opinion of the judge to give a decision in the case of running away from a girl who is not yet an adult is a matter of legal consideration based on legal facts in court to prove the guilt of the defendant